The chateau : a novel [large type] - Goldis, Jaclyn (Thorndike Press large print high octane, 2023)
"Welcome to picturesque Provence, where the Lady of the Chateau, Séraphine Demargelasse, has opened its elegant doors to her granddaughter Darcy and three friends. Twenty years earlier, the four girlfriends studied abroad together in France and visited the old woman on the weekends, creating the group's deep bond. But why this sudden invitation? Amid winery tours, market visits, and fancy dinners overlooking olive groves and lavender fields, it becomes clear that each woman has a hidden reason for returning to the estate after all these years. Then, following a wild evening's celebration, Séraphine is found brutally murdered. In the midst of this shocking crime, a sinister Instagram account pops up, exposing snapshots from the friends' intimate moments at the chateau, while threatening to reveal more. As they race to uncover who murdered Séraphine--and is now stalking them--the friends begin to suspect each other. Because the chateau houses many secrets...several worth killing for"--